Pendidikan Anti Korupsi Dan Integritas Pada Mahasiswa S1 Keperawatan Stikes Griya Husada Sumbawa - Asri Reni Handayani; Nurarifatus Sholihah; Ana Lestari; Rafi’ah Rafi’ah (Universitas Sains dan Teknologi Komputer, 2024)
Corruption has now become a cultural behavior, even a matter of debate and is always a hot topic, especially in Indonesia. In fact, corrupt practices are also rooted among students in various fields. Students can be said to be the seeds of corruption, if their behavior does not reflect anti-corruption behavior. This will affect the psychological condition of future generations of militants. Lack of supervision from both parents and educational institutions (campuses) is one of the factors causing corruption. The method for implementing anti-corruption education, which is based on the principle of building an anti-corruption culture, is a collaborative process, the implementation of which must involve students as agents of change. Anti-corruption education is considered to be one of the strategies for eradicating corruption because it can create an anti-corruption cultural ecosystem and strengthen the character of the younger generation. The aim of this community service activity is to increase the awareness and responsibility of students as the younger generation to behave anti-corruption and students are expected not to engage in corrupt practices even if the opportunity arises.